Use of triticale in the feeding of growing and fattening pigs (Semiárida, 2020)
Sixteen barrows triple crossed Hampshire x Duroc Jersey and Chester White x Duroc Jersey-Hampshire, were fed in individual boxes, from 30 to 95 Kg live weight, comparing two different diets with 8 pigs each: I, a complete diet based on triticale as sole grain, and II, a balanced commercial diet. The first one gave a greater intake (3,809 vs 3,600 Kg/day) though it was not really important. The daily gain and the feed/gain were favorable for the triticale diet during the growth (0,882 vs 0,800 Kg/day; 1: 3,027 vs 1:3,234 respectively) the fattening (0,814 vs 0,831 Kg/day; 1:4,107 vs 1:4,1 26 respectively) and for the trial period (8,863 vs 0,814 Kg/day; 1 :3.758vi 1:3,796 respectively) but without statistic signification in any of the cases. The animals corresponding to the first treatment showed less back fat thickness (25 vs 28 mm; P/0,05). The first diet gave better economic results than diet II considering the prices in force on-may 31st, 1985.
Keywords: pigs; triticale; alimentation